How unofficial media use shapes perceptions of political transparency: the mediating effect of subjective well-being and the moderating role of official media use among Chinese youth - Zhao, Xianlu; Waheed, Moniza; Ab Halim, Adlina; Tian, Zhuang; Yuan, Tao (Redfame Publishing, 2025)
This study examines the impact of unofficial media use on perceived government transparency in Chinese youth, focusing on the mediating role of subjective well-being and the moderating influence of official media use. Based on a cross-sectional survey of 405 participants aged 18-35 in Guangzhou, China, the results indicated that frequent use of unofficial media significantly reduced perceptions of political transparency, consistent with the media depression theory. In addition, subjective well-being played a critical mediating role in this relationship, while official media use mitigated the negative impact of unofficial media use. These results provide valuable insights into the role of the media in the political context and inform strategies for enhancing government transparency.